Foamed nickel carrier Fe-CaO bifunctional adsorption catalyst as well as preparation method and application thereof

By using a foam nickel-supported Fe-CaO dual-function adsorption catalyst, the problem of low CO2 conversion in the prior art was solved, and efficient CO2 capture and conversion was achieved, with a CO2 conversion rate reaching 84%, and good stability and selectivity were maintained.

CN119657150APending Publication Date: 2025-03-21NINGXIA HUI AUTONOMOUS REGION METROLOGY QUALITY INSPECTION & TESTING INST
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411913687.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The existing adsorption/catalytic bifunctional materials have low CO2 conversion rate and low resource utilization rate of carbon dioxide.

Method used

A two-functional adsorption catalyst for nickel foam supports, including CaO as an adsorbent and Fe+ as a catalyst, and is prepared by a simple one-step synthesis technology using nickel foam as a support.

Benefits of technology

The conversion rate of CO2 is significantly improved. The conversion rate of CO2 can reach 84%, the selectivity of CO is 100%, and the catalyst can maintain multiple cycles at high temperatures and has good stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119657150A_ABST
    Figure CN119657150A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of catalysts, and particularly relates to a foamed nickel carrier Fe-CaO bifunctional adsorption catalyst as well as a preparation method and application thereof. The bifunctional adsorption catalyst comprises an adsorbent, a catalyst and a carrier, the adsorbent comprises CaO, the catalyst comprises at least one of Fe < + > and Fe (NO3) 3, and the carrier comprises foamed nickel; the size of the bifunctional catalyst is 42-47nm, and the structure of the bifunctional catalyst is a rod-like structure formed by growing Fe-CaO powder on a foamed nickel skeleton; and the mass of Fe < + > in the catalyst is 0-11% of the mass of CaO. The bifunctional adsorption catalyst has a high CO2 conversion rate, and when CO2 is captured and converted into CO in situ, the CO2 conversion rate can reach 84%, and the CO selectivity is 100%. The preparation method of the foamed nickel carrier Fe-CaO bifunctional adsorption catalyst adopts a simple one-step synthesis technology, and is convenient and easy to implement.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalysts, and particularly relates to a foam nickel carrier Fe-CaO dual-function adsorption catalyst and a preparation method and application thereof. Background Art

[0002] With the rapid development of power generation, industrial manufacturing and transportation, the consumption of fossil fuels is increasing, the carbon dioxide emissions caused by human activities are growing rapidly, and the greenhouse effect is becoming more and more significant. Carbon dioxide capture, utilization and storage (CCUS) is one of the solutions to address global climate change. This type of technology takes carbon dioxide as the core and achieves the goal of emission reduction through the combination of multiple technical links.

[0003] In the prior art, the Chinese invention patent with application number 202211179942.1 discloses an integrated method for carbon dioxide capture and conversion based on adsorption / catalysis dual-functional materials, using alkali metal / alkaline earth metal-M / γ-Al 2 O 3 The adsorption catalytic system uses alkali metal / alkaline earth metal oxides as solid adsorbents to achieve chemical adsorption of carbon dioxide and generate carbonates; then the carbonates are hydrogenated to produce methane, and the solid adsorbent is regenerated under the action of the catalyst. The CO is converted into methane through the mutual conversion of alkali metal oxides / alkaline earth metal oxides and carbonates. 2 The capture and conversion of MOx-M can avoid the deactivation of the catalyst. However, the CO 2 The conversion rate is only 15.35% to 41.13%, and the resource utilization rate of carbon dioxide is low. Summary of the invention

[0004] Based on this, the present application provides a foam nickel carrier Fe-CaO dual-function adsorption catalyst and its preparation method and application to solve the problem of CO adsorption / catalysis dual-function materials in the prior art. 2 The technical problems are low conversion rate and low resource utilization rate of carbon dioxide.

[0005] The technical solution of this application to solve the above technical problems is as follows:

[0006] A foam nickel carrier Fe-CaO bifunctional adsorption catalyst, the bifunctional catalyst comprising an adsorbent, a catalyst and a carrier, wherein the adsorbent comprises CaO, the catalyst comprises Fe + 、Fe(NO 3 ) 3At least one of the above, wherein the carrier comprises nickel foam; the particle size of the bifunctional catalyst is 42 to 47 nm, and the structure is a rod-like structure formed by Fe-CaO powder growing on a nickel foam skeleton; the mass of Fe+ in the catalyst is 0% to 11% of the mass of CaO.

[0007] Preferably, the nickel foam carrier Fe-CaO bifunctional adsorption catalyst, the Fe + The mass of the CaO is 5% to 11% of the mass of the CaO.

[0008] Preferably, the method for preparing the above-mentioned nickel foam carrier Fe-CaO bifunctional adsorption catalyst comprises the following steps:

[0009] S10. The nickel foam was ultrasonically treated with hydrochloric acid and then with anhydrous ethanol, and then with deionized water. After the ultrasonic treatment, it was dried to obtain a pretreated nickel foam for standby use;

[0010] S20. Dissolve ferric nitrate nonahydrate, calcium nitrate tetrahydrate and urea in deionized water and stir to form a precursor mixture;

[0011] S30. Put the pretreated nickel foam and the precursor mixed solution into a reactor, react at 120 to 180° C. for 12 to 24 hours, then wash with anhydrous ethanol and deionized water to obtain a powder product, vacuum dry and calcine the powder product to obtain the nickel foam carrier Fe-CaO bifunctional adsorption catalyst.

[0012] Preferably, in the above preparation method, in step S20, in each milliliter of deionized water, the amount of ferric nitrate nonahydrate added is 0 g to 0.1 g, the amount of calcium nitrate tetrahydrate added is 0.2 g to 0.3 g, and the amount of urea added is 0.7 g to 0.8 g.

[0013] Preferably, in the above preparation method, in step S20, the concentration of urea is 3 to 6 mol / L.

[0014] Preferably, in the above preparation method, in step S30, referring to the amount of deionized water added in step S20, the amount of the pretreated nickel foam added is 3 to 5 g per milliliter of deionized water.

[0015] Preferably, in the above preparation method, step S10 is specifically as follows: the nickel foam is first soaked in 1M hydrochloric acid and ultrasonicated for 0.5 to 1 hour, then ultrasonicated with anhydrous ethanol for 0.5 to 1 hour, and then ultrasonicated with deionized water for 0.5 to 1 hour. After the ultrasonication, the nickel foam is placed in a 60°C oven and dried for 6 to 8 hours to obtain the pretreated nickel foam for later use.

[0016] A foam nickel carrier Fe-CaO dual-function adsorption catalyst as described above is used to capture CO2 The bifunctional adsorption catalyst was heated at 650 °C with 15% H 2 After pre-reduction for 1 to 2 hours, purge with nitrogen for 5 to 15 minutes; switch the flue gas produced by industrial cracking and coal combustion to CO 2 The mixture was collected for 40 to 50 min, and then purified with nitrogen for 5 to 15 min. H 2 Carry out hydrogenation reaction.

[0017] Preferably, in the above application, H is introduced into the hydrogenation reaction. 2 The concentration ranges from 15% to 100%.

[0018] The present invention adopts the above technical solution, and its beneficial effects are:

[0019] The present application discloses a foam nickel carrier Fe-CaO dual-function adsorption catalyst, comprising an adsorbent, a catalyst and a carrier, wherein the adsorbent comprises CaO, the catalyst comprises Fe + 、Fe(NO 3 ) 3 At least one of the above, the carrier comprises nickel foam; the particle size of the bifunctional catalyst is 42 to 47 nm, and the structure is a rod-like structure formed by Fe-CaO powder growing on a nickel foam skeleton; the Fe + The mass of the bifunctional adsorption catalyst is 0% to 11% of the mass of the CaO. 2 The conversion rate of CO 2 and converted into CO in situ, CO 2 The conversion rate can reach 84% and the CO selectivity is 100%.

[0020] The preparation method of the foam nickel carrier Fe-CaO bifunctional adsorption catalyst of the present application adopts a simple one-step synthesis technology, which is convenient and easy. The prepared bifunctional adsorption catalyst has a distinct microstructure, significant calcium oxide and calcium ferrite crystal forms, strong anti-methanization ability, and a selectivity of 100% for CO; it can still maintain multiple cycles at 0.1MPa, 650℃ high temperature and normal pressure, and the catalyst has a good conversion rate and stability during adsorption and catalysis, and can be used for a long time. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a structural diagram of the Fe-CaO bifunctional adsorption catalyst on a nickel foam carrier of the present application.

[0022] Figure 2 This is a flow chart of the preparation process of the nickel foam carrier Fe-CaO bifunctional adsorption catalyst of the present application.

[0023] Figure 3This is the XRD spectrum of the nickel foam carrier Fe-CaO bifunctional adsorption catalyst sample 2 of the present application. DETAILED DESCRIPTION

[0024] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present invention can be combined with each other. The technical solution of the present invention will be further described below in conjunction with the drawings of the embodiments of the present invention, and the present invention is not limited to the following specific implementation methods.

[0025] In a specific implementation of this application, please refer to Figure 1 A foam nickel carrier Fe-CaO bifunctional adsorption catalyst (hereinafter referred to as bifunctional catalyst), the bifunctional catalyst comprises an adsorbent, a catalyst and a carrier, wherein the adsorbent comprises CaO, the catalyst comprises Fe + 、Fe(NO 3 ) 3 At least one of the carriers includes nickel foam; the bifunctional catalyst has a particle size of 42 to 47 nm, and a structure of a rod-shaped structure formed by Fe-CaO powder growing on a nickel foam skeleton; the mass of Fe+ in the catalyst is 0% to 11% of the mass of CaO. Carbon dioxide capture methods include: before combustion, after combustion based on chemical absorption, physical separation, membrane separation, chemical cycle combustion, calcium cycle process and oxygen-enriched combustion. Among them, calcium cycle capture is an effective way to achieve carbon dioxide capture and in-situ conversion. The material used has both adsorption and catalytic functions, and is called a bifunctional adsorption catalyst. The composition of the bifunctional adsorption catalyst of the present application is Fe-CaO / NiO-foam, wherein Fe + The precursor of the metal active phase and the auxiliary agent in the adsorption catalyst is water-soluble iron nitrate, CaO indicates that the precursor of the adsorbent and the active material is water-soluble calcium nitrate; NiO-foam indicates that the metal auxiliary agent and the carrier exist in the solution in solid form. The bifunctional adsorption catalyst has high CO 2 The conversion rate of CO 2 and converted into CO in situ, CO 2 The conversion rate is 52% to 84%, and the selectivity of CO is 100%. Preferably, Fe + The mass of CO is 5% to 11% of the mass of CaO. 2 The conversion rate is 67% to 84%; further, the Fe + The mass of CO is 5% of the mass of CaO. 2 The conversion rate was 84%.

[0026] In a specific implementation of this application, please refer to Figure 2The preparation method of the above-mentioned nickel foam carrier Fe-CaO bifunctional adsorption catalyst comprises the following steps:

[0027] S10. The nickel foam was ultrasonically treated with hydrochloric acid and then with anhydrous ethanol, and then with deionized water. After the ultrasonic treatment, it was dried to obtain a pretreated nickel foam for standby use;

[0028] Specifically, the nickel foam is first soaked in 1M hydrochloric acid and ultrasonicated for 0.5 to 1 hour, then ultrasonicated in anhydrous ethanol for 0.5 to 1 hour, and then ultrasonicated in deionized water for 0.5 to 1 hour. After the ultrasonication, the nickel foam is placed in a 60°C oven and dried for 6 to 8 hours to obtain the pretreated nickel foam for later use. It should be noted that each time the solvent is switched, the solvent of the previous step is first cleaned with the solvent of the next step.

[0029] S20. Dissolve ferric nitrate nonahydrate, calcium nitrate tetrahydrate and urea in deionized water and stir to form a precursor mixture; wherein ferric nitrate nonahydrate Fe(NO 3 ) 3 9H 2 O is Fe in the adsorbent + The main source of calcium nitrate tetrahydrate Ca(NO 3 ) 2 ·4H 2 O is the main source of Ca in the catalyst, urea CO(NH 2 ) 2 As a reducing agent. + The mass of is 0% to 11% of the mass of the CaO. Further, for each milliliter of deionized water, the amount of ferric nitrate nonahydrate added is 0 to 0.1 g, the amount of calcium nitrate tetrahydrate added is 0.2 to 0.3 g, the amount of urea added is 0.7 to 0.8 g, and the concentration of urea is 3 to 6 mol / L.

[0030] S30. Put the pretreated nickel foam and the precursor mixed solution into a reactor, react at 120 to 180° C. for 12 to 24 hours, then wash with anhydrous ethanol and deionized water to obtain a powder product, vacuum dry and calcine the powder product to obtain the nickel foam carrier Fe-CaO bifunctional adsorption catalyst. Preferably, referring to the amount of deionized water added in step S20, the amount of the pretreated nickel foam added to each milliliter of deionized water is 3 to 5 g.

[0031] For example, 3 to 5 g of the pretreated nickel foam and a precursor mixed liquid are placed in a polytetrafluoroethylene reactor and placed in an oven at 180°C for 12 hours to obtain a powder product; the powder product is washed with anhydrous ethanol and deionized water, placed in a vacuum drying oven at 60°C, and then calcined at 750 to 850°C to obtain a nickel foam carrier Fe-CaO bifunctional adsorption catalyst.

[0032] A foam nickel carrier Fe-CaO dual-function adsorption catalyst as described above is used to capture CO 2 The bifunctional adsorption catalyst was heated at 650 °C with 15% H 2 After pre-reduction for 1 to 2 hours, purge with nitrogen for 5 to 15 minutes; switch the flue gas produced by industrial cracking and coal combustion to CO 2 The mixture was collected for 40 to 50 min, and then purified with nitrogen for 5 to 15 min. H 2 Experiments have shown that H 2 Effect of CO concentration on the bifunctional adsorption catalyst 2 The in situ transformation effect of H 2 When the concentration is 15%, CO 2 The conversion rate was 62%. 2 When the concentration is 80% to 100%, CO 2 The conversion rate is 84%. Therefore, preferably, H is introduced into the hydrogenation reaction. 2 The concentration ranges from 15% to 100%.

[0033] It is worth noting that the process temperature and process time involved in the above-mentioned embodiments are all temperatures or times used in the experimental process. Those skilled in the art can make reasonable adjustments within the error range based on the process temperature and process time provided by the present invention, which should be included in the protection scope of the present invention.

[0034] The technical solution and technical effects of the present invention are further illustrated below through specific experimental examples.

[0035] 1. Main reagents

[0036] It should be noted that in the examples of the present invention, all reagents and solvents are commercially available and can be used without further purification.

[0037] 2. Pretreatment of nickel foam carrier: 0.4 g nickel foam was placed in a 100 mL beaker, first soaked in 1 M hydrochloric acid and ultrasonicated for 0.5 to 1 h, then ultrasonicated in anhydrous ethanol for 0.5 to 1 h, and then ultrasonicated in deionized water for 0.5 to 1 h. After the ultrasonication, it was placed in a 60 ° C oven and dried for 6 to 8 h to obtain pretreated nickel foam.

[0038] 3. Comparative ratio

[0039] 8.43 g of calcium nitrate tetrahydrate and 1.37 g of ferric nitrate nonahydrate were dissolved in 35 mL of deionized water to obtain a precursor mixed solution; 0.4 g of the pretreated nickel foam was placed in a polytetrafluoroethylene reactor together with the precursor mixed solution, and placed in an oven at 180°C for 12 hours. The obtained powder product was washed with 500 mL of anhydrous ethanol and 500 mL of deionized water, vacuum dried overnight, and then calcined at 750°C for 2 hours to obtain a bifunctional adsorption catalyst.

[0040] 4. Embodiment 1

[0041] 8.43 g of calcium nitrate tetrahydrate, ferric nitrate nonahydrate of the mass shown in Table 1, and 11.15 g of urea (concentration of 6 mol / L) were dissolved in 35 mL of deionized water to obtain a precursor mixed solution; 0.4 g of the pretreated nickel foam was placed in a polytetrafluoroethylene reactor together with the precursor mixed solution, and placed in an oven at 180°C for 12 hours. The obtained powder product was washed with 500 mL of anhydrous ethanol and 500 mL of deionized water, vacuum dried overnight, and then calcined at 750°C for 2 hours to obtain a bifunctional adsorption catalyst, which was marked as sample 1 to sample 3 for easy distinction.

[0042] Table 1 Comparative Example and Example 1 Raw Material Amounts

[0043]

[0044]

[0045] The bifunctional adsorption catalyst prepared in the comparative example and Example 1 was heated at 650°C with 15% H 2 After 1.5 h of pre-reduction, nitrogen was purged for 10 min; 10% CO 2 / N 2 CO 2 The mixture was collected for 45 min, then purified with nitrogen for 10 min, and 15% H 2 The hydrogenation reaction was carried out at a flow rate of 100 mL / min and a pressure of 0.1 MPa. The adsorption catalytic performance of the above-mentioned bifunctional adsorption catalyst was then evaluated. The specific method is referred to "Preparation of Ni-CaO bifunctional materials using different synthesis methods for integrated CO 2 Capture and transformation》Wang Guang, Guo Yu, Yu Jie, Liu Feng, Sun Jie, Wang Xiao, Wang Tian, ​​etc., supervised by Zhao Cheng. Journal of Chemical Engineering, 2022, 428, 132110.474. Experimental data are shown in Table 2:

[0046] Table 2 Performance parameters of samples of comparative example and embodiment 1

[0047]

[0048] As can be seen from the table above, the comparative sample, that is, no urea was added to the precursor mixture, and the adsorption catalytic performance of the obtained bifunctional adsorption catalyst was the worst; sample 1, that is, the addition amount of ferric nitrate nonahydrate was 0, the adsorption catalytic performance was improved compared with the comparative sample, but it was worse than sample 2 and sample 3, which may be due to the lack of catalyst leading to CO 2 The adsorption catalytic performance of sample 2 (XRD spectrum see Figure 3 ), when the amount of ferric nitrate nonahydrate added increases to Fe + When the percentage of CaO is 5%, CO 2 The adsorption amount, CO production and CO 2 The conversion rates all reached high values, among which CO 2 The conversion rate was 70%, which was higher than that of the comparative sample CO 2 The conversion rate increased by 21%, and the improvement rate was 42.8%; compared with sample 1, CO 2 The conversion rate increased by 18%, and the improvement rate was 34.6%. As the amount of ferric nitrate nonahydrate added continued to increase, that is, sample 3, the adsorption catalytic performance was maintained at a relatively good level, but it was lower than that of sample 2. It can be seen that sample 2, namely Fe + When the percentage of CaO is 5%, the adsorption catalytic performance of the bifunctional adsorption catalyst is optimal.

[0049] 5. Example 2

[0050] The preparation method is the same as that of sample 2, except that the concentrations of urea are 3 mol / L and 8 mol / L respectively. The prepared bifunctional adsorption catalysts are marked as sample 4 and sample 5.

[0051] The above samples were heated at 650°C with 15% H 2 After 1.5 h of pre-reduction, nitrogen was purged for 10 min; 10% CO 2 / N 2 CO 2 The mixture was collected for 45 min, then purified with nitrogen for 10 min, and 15% H 2 The hydrogenation reaction was carried out at a flow rate of 100 mL / min and a pressure of 0.1 MPa. Then, the adsorption catalytic performance of the above-mentioned bifunctional adsorption catalyst was evaluated. The specific method was the same as that of Example 1. The experimental data are shown in Table 3:

[0052] Table 3 Performance parameters of samples in Example 2

[0053]

[0054] Please refer to Table 3. When the concentration of urea in the precursor mixed solution is changed, the adsorption catalytic performance of the prepared bifunctional adsorption catalyst will also change. The adsorption catalytic performance of sample 4 and sample 5 is not much different, but it is significantly different from sample 2. The CO of sample 2 2 The conversion rate is 70%, while that of sample 4 and sample 5 is only 60% to 62%, indicating that the urea concentration is too low or too high, and the adsorption catalytic performance of the obtained bifunctional adsorption catalyst is not ideal. A urea concentration of 6 mol / L is the best choice.

[0055] 6. Example 3

[0056] Four groups of bifunctional adsorption catalyst samples were prepared using the same preparation method as Sample 2, and were labeled as Sample 6, Sample 7, Sample 8, and Sample 9, respectively.

[0057] The above samples were heated at 650°C with 15% H 2 After 1.5 h of pre-reduction, nitrogen was purged for 10 min; 10% CO 2 / N 2 CO 2 The trapping was carried out for 45 min, followed by nitrogen purification for 10 min, and H concentrations shown in Table 4 were introduced. 2 The hydrogenation reaction was carried out at a flow rate of 100 mL / min and a pressure of 0.1 MPa. Then, the adsorption catalytic performance of the above-mentioned bifunctional adsorption catalyst was evaluated. The specific method was the same as that of Example 1. The experimental data are shown in Table 4:

[0058] Table 4 Performance parameters of samples in Example 3

[0059]

[0060] It can be seen from Table 4 that in the hydrogenation reaction, as H 2 With the increase of the concentration of , the adsorption catalytic performance of the bifunctional adsorption catalyst also improves. 2 When the concentration is 15%, CO 2 The conversion rate was 70%. 2 When the concentration is 34%, CO 2 The conversion rate was 79%, which was further improved than that of sample 2. 2 When the concentration is higher than 55%, CO 2 The conversion rate reached more than 80%; when H 2 When the concentration is 80% to 100%, CO 2 The conversion rate was maintained at 84%. 2 The concentration can be preferably 55% to 80%, at which point CO 2 The conversion rate is over 80% and it saves more H than 100% 2Dosage.

[0061] In order to verify the stability of the bifunctional adsorption catalyst of the present application, sample 7 was used with a hydrogenation concentration of 55%. After 12 cycles, the CO 2 The adsorption capacity was 6.2mmol / g, the CO production was 5.5mmol / g, and the CO 2 The conversion rate is 80% and the CO selectivity is 100%. In other words, the bifunctional adsorption catalyst of the present application can efficiently capture CO 2 And convert it into CO, with a selectivity of 100% and no byproduct methane. According to the test, the CO production increases with the increase of hydrogen concentration under different hydrogen concentration conditions, and the unreacted carbon dioxide also decreases. The adsorption amount is 12.8mmol / g, and the CO production reaches 8.67mmol / g under the condition of 80% hydrogen content, and the conversion rate reaches 84%. The CO production reaches 9.01mmol / g under the condition of 55% hydrogen content, and the conversion rate reaches 81%, and it can still maintain 80% CO under the condition of 12 cycles. 2 Conversion rate, good stability, and can be used for a long time.

[0062] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A nickel foam carrier Fe-CaO bifunctional adsorption catalyst, characterized in that: The bifunctional catalyst comprises an adsorbent, a catalyst and a carrier, wherein the adsorbent comprises CaO, the catalyst comprises Fe + , Fe(NO3)3, the carrier comprises nickel foam; the particle size of the bifunctional catalyst is 42 to 47 nm, and the structure is a rod-like structure formed by Fe-CaO powder growing on a nickel foam skeleton; the Fe + The mass of the CaO is 0% to 11% of the mass of the CaO.

2. The nickel foam carrier Fe-CaO bifunctional adsorption catalyst according to claim 1, characterized in that: The Fe + The mass of the CaO is 5% to 11% of the mass of the CaO.

3. A method for preparing the Fe-CaO bifunctional adsorption catalyst on a nickel foam carrier as claimed in claim 1, characterized in that: The following steps are involved: S10. The nickel foam was ultrasonically treated with hydrochloric acid and then with anhydrous ethanol, and then with deionized water. After the ultrasonic treatment, it was dried to obtain a pretreated nickel foam for later use; S20. Dissolve ferric nitrate nonahydrate, calcium nitrate tetrahydrate and urea in deionized water and stir to form a precursor mixture; S30. Put the pretreated nickel foam and the precursor mixed solution into a reactor, react at 120 to 180° C. for 12 to 24 hours, then wash with anhydrous ethanol and deionized water to obtain a powder product, vacuum dry and calcine the powder product to obtain the nickel foam carrier Fe-CaO bifunctional adsorption catalyst.

4. The preparation method according to claim 3, characterized in that: In step S20, in each milliliter of deionized water, the amount of ferric nitrate nonahydrate added is 0 g to 0.1 g, the amount of calcium nitrate tetrahydrate added is 0.2 g to 0.3 g, and the amount of urea added is 0.7 g to 0.8 g.

5. The preparation method according to claim 3, characterized in that: In step S20, the concentration of urea is 3 to 6 mol / L.

6. The preparation method according to claim 3, characterized in that: In step S30, referring to the amount of deionized water added in step S20, the amount of the pretreated nickel foam added is 3 to 5 g per milliliter of deionized water.

7. The preparation method according to claim 3, characterized in that: Step S10 is specifically as follows: soaking the nickel foam in 1M hydrochloric acid and ultrasonicating for 0.5 to 1 hour, then ultrasonicating with anhydrous ethanol for 0.5 to 1 hour, and then ultrasonicating with deionized water for 0.5 to 1 hour. After the ultrasonication, the nickel foam is placed in a 60° C. oven and dried for 6 to 8 hours to obtain the pretreated nickel foam for later use.

8. Use of the nickel foam carrier Fe-CaO bifunctional adsorption catalyst as claimed in claim 1 or 2 in capturing CO2 and converting it into CO in situ, characterized in that: The bifunctional adsorption catalyst was pre-reduced with 15% H2 at 650°C for 1 to 2 hours, and then purged with nitrogen for 5 to 15 minutes; the flue gas produced by industrial cracking and coal combustion was switched to capture CO2 for 40 to 50 minutes, followed by nitrogen purification for 5 to 15 minutes, and H2 was introduced for hydrogenation reaction.

9. The use according to claim 8, characterized in that The concentration of H2 introduced into the hydrogenation reaction is 15% to 100%.

Citation Information

Patent Citations

  • Carbon dioxide capture and conversion integrated implementation method based on adsorption / catalysis bifunctional material

    CN115555016A